2011
DOI: 10.1007/s00216-011-5483-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional HPLC coupled to ICP-MS and electrospray ionisation (ESI)-MS/MS for investigating the bioavailability in vitro of arsenic species from edible seaweed

Abstract: Edible seaweed consumption is a route of exposure to arsenic. However, little attention has been paid to estimate the bioaccessibility and/or bioavailability of arsenosugars in edible seaweed and their possible degradation products during gastrointestinal digestion. This work presents first use of combined inductively coupled plasma mass spectroscopy (ICP-MS) with electrospray ionization tandem mass spectrometry (ESI-MS/MS) with two-dimensional HPLC (size exclusion followed by anion exchange) to compare the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The concentrations were comparable with concentrations found by some researchers but much lower compared with others (Laparra et al 2003;Wei et al 2003;Koch et al 2007;Rose et al 2007;Nakamura et al 2008;LlorenteMirandes et al 2011;Garcia-Sartal et al 2012;Oguri et al 2014). In the current study, not many seaweed products were investigated, but the products investigated were obtained from different shops throughout the Netherlands and were imported from regions in the world with high As levels.…”
Section: As and As Species Concentrations In Foodsupporting
confidence: 88%
“…The concentrations were comparable with concentrations found by some researchers but much lower compared with others (Laparra et al 2003;Wei et al 2003;Koch et al 2007;Rose et al 2007;Nakamura et al 2008;LlorenteMirandes et al 2011;Garcia-Sartal et al 2012;Oguri et al 2014). In the current study, not many seaweed products were investigated, but the products investigated were obtained from different shops throughout the Netherlands and were imported from regions in the world with high As levels.…”
Section: As and As Species Concentrations In Foodsupporting
confidence: 88%
“…Williams et al (2009), Maulvault et al (2011), and Garcia-Sartal et al (2012 provided estimates of the bioaccessibility of total As, which do not support evaluation of iAs risks. Oguri et al, 2014 provided estimates of the amount of bioaccessible iAs consumed daily, which is of interest in estimating risks associated with dietary consumption of iAs.…”
Section: Arsenic Bioaccessibility In Seafoodmentioning
confidence: 98%
“…Five studies were identified that examined As bioaccessibility in marine seafood and seaweed, and in freshwater crayfish using in vitro test systems (Leufroy et al, 2012;Williams et al, 2009;Maulvault et al, 2011;Garcia-Sartal et al, 2012;Oguri et al, 2014). Leufroy et al (2012) used a continuous leaching procedure adapted from Dufailly et al (2008) comprising saliva, gastric and intestinal phases to assess As bioaccessibility in 30 seafood samples consisting of mussel, scallop, shrimp, crab, periwinkle, saithe, salmon, smoked salmon, tuna and canned tuna.…”
Section: Arsenic Bioaccessibility In Seafoodmentioning
confidence: 99%
See 1 more Smart Citation
“…By estimating As bioaccessibility through the human GI tract using modifications of methods developed by nutritionists for estimating Fe uptake, Garcia-Sartal et al (2012) concluded that only a fraction (7–15%) of the inorganic As and arsenosugars in cooked algae such as kombu, wakame, nori, and sea lettuce is bioaccessible. More research is needed to understand how different cooking processes, the particular algal food matrix, and the gut microbiome modify arsenosugar bioaccessibility and then better definition of the interaction of other As species produced in the body with cellular metabolites and macromolecules before their excretion (NRC 2013; Molin et al 2015; Carlin et al 2016).…”
Section: Safetymentioning
confidence: 99%